Efficacy of Streptococcus agalactiae vaccine strains N3M and N4M in fry tilapia infected by different strains of S. agalactiae - Sukenda, Sukenda; Arif Lukman Firmansyah; Rahman, Rahman; Sri Nuryati; Dendi Hidayatullah (Jurnal Akuakultur Indonesia)
ABSTRACT